ANALISIS HUBUNGAN KEDISIPLINAN DAN KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DALAM UPAYA PENINGKATAN KINERJA ORGANISASI BADAN PERTANAHAN NASIONAL KANTOR WILAYAH PROVINSI JAWA TENGAH - Idham Hadiguna; Nina Widowati; Susi Sulandari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
This study aims to describe the performance of the National Land Agency Of Central Java Province and to know the corelations of discpline and leadership to employee performance in an effort to improve organizatinal in National Land Agency Of Central Java Province. Locus were used in this research is National Land Agency Of Central Java Province. This research uses quanitative research methods are purely eexplanation. The respondents in this study consists of 44 (fourty four) employees National Land Agency Of Central Java Province.Based on the research results show that the performance of the National Land Agency Of Central Java Province can be categorized good. Either even though there is still some indicators assessed less optimally. Aspects that affect optimally performance of National Land Agency Of Central Java Province which aspects of discipline and leadership aspects.Conclusions in this study was the overall performance of the National Land Agency Of Central Java Province was good, and the aspect of the discipline and leadership indeed affect National Land Agency Of Central Java Province.Based on the conclusions, researchers recommended National Land Agency Of Central Java Province to fix indicators is still less than optimalso that more optimal performance can be achieved.